Project on Human Development in Chicago Neighborhoods (PHDCN): Peabody Picture Vocabulary Test, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the The Peabody Picture Vocabulary Test (PPVT). It was designed as a test of receptive vocabulary achievement and verbal ability and was administered to subjects in Cohort 0. Subjects were shown four numbered pictures and were read a word by a research assistant. The subject was then asked to point to the picture or say the number of the picture that corresponded to the word spoken by the research assistant.